KEWARGANEGARAAN AFEKTIF DALAM PENDIDIKAN MULTIKULTURAL: PERSPEKTIF MICHALINOS ZEMBYLAS - Yaya Mulya Mantri; Deni Ramdani (Universitas Nias Raya, 2026)
Affective citizenship is essential in multicultural societies to mitigate social conflicts. This study aims to analyze the urgency and implementation of affective citizenship in education. Employing a qualitative method through library research, data were collected from literature regarding the work of Michalinos Zembylas and other relevant scholars. Data were analyzed using content analysis and verified through source triangulation. The results indicate that citizenship is not merely an administrative status but an emotional bond involving love, loyalty, and empathy that is crucial in multicultural education. The study concludes that integrating affective dimensions into pedagogy fosters solidarity and inclusive citizenship. It is recommended that educators actively cultivate a classroom climate that facilitates positive emotional engagement among students to strengthen social cohesion in diverse school environments.